"Candidatus Campylobacter infans" detection is not associated with diarrhea in children under the age of 2 in Peru. - Paul F Garcia Bardales; Francesca Schiaffino; Steven Huynh; Maribel Paredes Olortegui; Pablo Peñataro Yori; Tackeshy Pinedo Vasquez; Katia Manzanares Villanueva; Greisi E Curico Huansi; Wagner V Shapiama Lopez; Kerry K Cooper; Craig T Parker; Margaret N Kosek (Public Library of Science (PLoS), 2022)
A working hypothesis is that less common species of Campylobacter (other than C. jejuni and C. coli) play a role in enteric disease among children in low resource settings and explain the gap between the detection of Campylobacter using culture and culture independent methods. "Candidatus Campylobacter infans" (C. infans), was recently detected in stool samples from children and hypothesized to play a role in Campylobacter epidemiology in low- and middle-income countries (LMIC). This study determined the prevalence of C. infans in symptomatic and asymptomatic stool samples from children living in Iquitos, Peru. Stool samples from 215 children with diarrhea and 50 stool samples from children without diarrhea under the age of two were evaluated using a multiplex qPCR assay to detect Campylobacter spp. (16S rRNA), Campylobacter jejuni / Campylobacter coli (cadF gene), C. infans (lpxA), and Shigella spp. (ipaH). C. infans was detected in 7.9% (17/215) symptomatic samples and 4.0% (2/50) asymptomatic samples. The association between diarrhea and the presence of these targets was evaluated using univariate logistic regressions. C. infans was not associated with diarrhea. Fifty-one percent (75/146) of Campylobacter positive fecal samples were negative for C. jejuni, C. coli, and C. infans via qPCR. Shotgun metagenomics confirmed the presence of C. infans among 13 out of 14 positive C. infans positive stool samples. C infans explained only 20.7% of the diagnostic gap in stools from children with diarrhea and 16.7% of the gap in children without diarrhea. We posit that poor cadF primer performance better explains the observed gap than the prevalence of atypical non-C. jejuni/coli species.